Evaluation of Compliance with the Fundamentals of Preference of Certainty over Severity of Punishment in Sentencing Criminal code of Afghanistan - with an Emphasis on Administrative Corruption Crimes - Mohammad Iqbal Haqyar; Syed Baqer Mohammadi (مطالعات تطبیقی حقوق کشورهای اسلامی)
Despite the fact that with the implementation of the penal code, the country's criminal policy went down in terms of quantity and quality; There is basically no relationship between the severity of the punishment and the achievement of the goal.in specific crimes such as crimes against internal and external security or crimes of administrative corruption, the country's criminal policy is different and in this context, the scope of crime is wider and the punishments are more severe.The purposeful penalization model means policy making in the field of punishment, both in terms of type and amount, based on a predictable and systematic logic, and penological and criminological scientific teachings play a prominent role in it.This model is proposed in the direction of organizing punishments and moving away from stereotyped punishments, which has its own fundamentals, and its executive measures should be planned according to these fundamentals that one of them is "improving certainty over the severity of punishment".This work has evaluated how to comply with the fundamental of preference of certainty over severity of punishment in the penal code of Afghanistan from the perspective of the mentioned model with emphasis on administrative corruption crimes and found that the fundamental of preference of certainty over severity of punishment in 14 discourses which includes 5 discourses of general sentences and 9 discourses of crimes and punishments (administrative corruption) has not been observed.